Resetting and Entrainment of Reentrant Arrhythmias: Part I: Concepts, Recognition, and Protocol for Evaluation: Surface ECG versus Intracardiac Recordings - ALMENDRAL, JESÚS (Blackwell Publishing Ltd, 2013)
In this paper, we review the information accumulated over the years regarding the phenomena of resetting and entrainment of reentrant arrhythmias. Over three decades of research and clinical applications, these phenomena have demonstrated that they stay as a main tool for an intellectual understanding of reentry and to base strategies for localization of critical areas for ablative therapies. This review will be divided into two parts. This first part deals with the bases for the concept development, the means for the detection of these phenomena, and their mechanistic implications. Resetting is described as a particular response of a given rhythm to an external perturbation, indicating interaction between them. Entrainment indicates continuous reset of the rhythm when the perturbation is repetitive. The mechanisms that explain these responses in reentrant rhythms are presented. Fusion, both at the surface electrocardiogram and at the level of intracardiac recordings, is discussed in detail, with its value and limitations as a key concept to recognize entrainment and reentry. Computer simulations are used as an aid to a better understanding. Differences between resetting and entrainment are considered, and a pacing protocol to study these phenomena described.